2020
DOI: 10.3390/su12198026
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk of Natural Disaster-Induced Losses to Tunnel-Construction Projects Using Empirical Financial-Loss Data from South Korea

Abstract: Tunnel construction, a common byproduct of rapid economic growth and transportation-system development, carries inherent risks to life and various kinds of property that operations and management professionals must take into account. Due to various and complicated geological conditions, tunnel construction projects can produce unexpected collapses, landslides, avalanches, and water-related hazards. Moreover, damage from such events can be intensified by other factors, including geological hazards caused by nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…The DNN model revealed that natural disasters could be associated with financial losses. This finding can be utilized for mitigating unexpected risks such as financial losses since natural disasters would be the strongest influential factors for losses at construction projects [13]. Future construction projects can utilize findings of this study to cope with various possible natural hazards for preventing unexpected financial losses while considering additional more specific construction site-oriented variables such as geographical and local weather.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The DNN model revealed that natural disasters could be associated with financial losses. This finding can be utilized for mitigating unexpected risks such as financial losses since natural disasters would be the strongest influential factors for losses at construction projects [13]. Future construction projects can utilize findings of this study to cope with various possible natural hazards for preventing unexpected financial losses while considering additional more specific construction site-oriented variables such as geographical and local weather.…”
Section: Discussionmentioning
confidence: 81%
“…Considering that the ultimate goal of risk analysis is the efficient allocation and input of defined resources, quantitative methodology is more suitable for risk analysis. In addition, the quantitative methodology enables a more realistic and accurate analysis of the potential risks of construction sites and enables higher generalization [13]. Furthermore, through the introduction of a quantitative risk analysis methodology, potential risk factors can be identified, factors indexed, and quantified models can be developed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction vulnerability reflects the different resistance of different railway constructions with respect to specific geohazards [44]. To estimate the construction vulnerability, a simple but effective score ranking method is proposed.…”
Section: Spatial Geohazard Assessment 331 Spatial Construction Vulmentioning
confidence: 99%
“…For the quantitative and objective assessment of natural hazards, the risk rating of the Munich Reinsurance Company's Natural Risk Assessment Network (NATHAN) was adopted. NATHAN was developed through a comprehensive analysis of public sources, scientific analyses, and the severity and frequency of past natural hazards, aimed at estimating the risk of natural hazards around the world through the risk of various natural hazards according to geographical locations [23]. The risk rating of each natural disaster was used as the nominal variable.…”
Section: Maintenance and Repair Cost Ratio =mentioning
confidence: 99%